Parameter calibration of discrete element model for alfalfa seeds based on EDEM simulation experiments - Zhang, Xinjiu; Wang, Hongti; Wang, Fangyan; Lian, Zhengguo (International Journal of Agricultural and Biological Engineering, 2024)
In order to establish an accurate discrete element model of alfalfa seeds, real physical experiments were combined with simulation experiments, and the contact parameters of alfalfa seeds were calibrated using the repose angle of alfalfa seeds as the response value. Some intrinsic parameters (thousand grain weight, triaxial size, density) and contact parameters (static friction coefficient, rolling friction coefficient) of alfalfa seeds were obtained through physical experiments, and a spherical particle model was established. Through the Plackett Burman experiment, the static friction coefficient between alfalfa seeds, the rolling friction coefficient between alfalfa seeds, and the static friction coefficient between alfalfa seeds and ABS plastic were determined to have a significant impact on the experiment. The steepest climb test is used to narrow down the selection range of the optimal parameters, and the box Behnken test is used to obtain the quadratic regression equation of the repose angle. The optimal parameter combination was obtained with the objective of minimizing the repose angle error: the static friction coefficient between alfalfa seeds and alfalfa seeds was 0.418, the rolling friction coefficient between alfalfa seeds and alfalfa seeds was 0.086, and the static friction coefficient between alfalfa seeds and ABS plastic was 0.471. The repose angle and mass flow rate experiments show that the model is effective and reliable. Keywords: alfalfa seeds, discrete element, parameter calibration, EDEM DOI: 10.25165/j.ijabe.20241703.8681 Citation: Zhang X J, Wang H T, Wang F Y, Lian Z G. Parameter calibration of discrete element model for alfalfa seeds based on EDEM simulation experiments. Int J Agric & Biol Eng, 2024; 17(3): 33-38.